Diversity And Abundance Of Macrozoobentos And Pisces In The Mangrove Area Of Gresik District, Kebomas And Manyar Gresik Regency - Vidia Kristanti; Diah Karunia Binawati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
Mangrove ecosystems play an important role in the life cycle of various types of fish, shrimp and crabs. Because the mangrove environment provides protection and nutrients in the form of organic matter that is included in the food chain. Some of the fauna that are commonly found in the Indonesian mangrove ecosystem area are fauna from the gastropod, crustacean, bivalve, polychaeta, and pisces classes. One of the biota that can be used as biological parameters in determining the conditions of a body of water is macrozoobentos. As organisms living in waters, macrozoobentos are very sensitive to changes in the quality of the water in which they live so that it will affect their composition and abundance. This research method is quantitative descriptive research by taking data in a survey. It uses a 1x1m measuring plot 100m long perpendicular to the coastline. The measurement method used to determine the environmental conditions of mangroves is the transect line method and sample plots (Tran-sect Line Plot). The diversity index value at research locations I and II is in the medium category, while in location III it is in the high category. Of the three stations, the uniformity index is stable close to 1. Result The dominance index value is that there is no type that dominates a body of water, this means that all individuals at the observation station have the same opportunity and maximally make the most of the resources in those waters. The pH results of water at station II and station III did not differ significantly, while at station I it differed significantly when compared to the results at stations II and III. The salinity results at station III differ significantly from station I and II because the location of the mangrove is the location of a sea estuary that makes the salt content of brackish water mixed with fresh water.    Keywords ; Mangroves, Macrozoobentos, Diversity, Uniformity, Dominance, Abundance, Abiotic Factors